London - being in the library. David Adjaye and Philip Ursprung in conversation. - Adjaye, David; Ursprung, Philip (Park Books, 2021)
Daniela Keiser is among the most renowned contemporary artists in Switzerland. In 2017 she was awarded the Prix Meret Oppenheim, and a studio grant from Landis & Gyr Stiftung that offered her an extended stay in London’s East End. There she discovered the Idea Store, the public library on Whitechapel Road, built by British architect David Adjaye in 2001–05. Upon its opening to the public this institution quickly became a meeting place also for socially disadvantaged people. The goal of the Idea Stores - eight of them have currently been opened in various London boroughs - is to upgrade neglected neighborhoods and offer a low-threshold source of education and information. From that initial Idea Store on Whitechapel Road, Daniela Keiser began to take pictures of the goings-on in the street outside. Her Library - Idea Store series reveals a calm, repetitive insistent image and offers insight into the everyday variations in the surroundings. Her photographic reflection is accompanied by a conversation with David Adjaye conducted by art and architecture historian Philip Ursprung. They talk about Keiser’s perception of the site and - without actually showing the building - the impact of urban design and the architect’s intentions.
Keywords: Kunst; Fotografie; Reflexion; Situationsanalyse; Variabilität; Stadtleben; Alltagsleben; Stadtviertel; Bebauung; Umgebung; Standort; Bibliothek; Stadtraum; Tageszeit; Uhrzeit